(untitled) (Global Journal of Management and Business Research, 2020)
Exceptional alternative investments are compatible with investments other than public real estate, equity and debt. It includes investments from private property, hedge funds and managed futures, water equity, and real property and natural resource cooperation. In addition, the alternative investment industry starts fast - it grows and expands its ability to provide long term investment strategies, thereby attracting interest from a growing number of investors. Investments other than these three traditional assets: cash, bonds and stocks are known as separate investments. This investment comes with the promise of greater returns, however, it is risky. The dangerous nature of these goods can be tied to the fact that they are not regulated, unlike the classes of traditional goods. On the other hand, alternative investments can be classified as tangible and intangible investments. Some examples of tangible investments others are Wine, Stamps, Fine Art, Antique, Jewellery. examples of intangible investments are Hedge funds, Independent equity, Venture capital, Cryptocurrency